Histopathological Study Of Naturally Occurring Pathological Conditions Of Uterus Affecting Reproduction In Small Ruminants - Agarwal, J.K.; Vashistha, N.K.; Sharma, Amit; Sharma, Rinku; Singh, M.M.; Kumar , Pravesh (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The study was conducted to assess the histopathology of genital tract diseases of small ruminants (n=638; sheep 267 and goats 371). Out of the total sheep and goat genitalia examined, 19 (7.11%) and 30 (8.08%), respectively, had uterine abnormalities. Pregnancy was recorded in 11.59 per cent of the abattoir goat genitalia and 7.86 per cent of ewe genitalia. Histopathologically, gravid uterus revealed an increase in the size and number of endometrial glands, sparse stroma and increased cellularity of the surface epithelium. Uterus with pyometra revealed dilated and hyperplastic endothelial glands variably filled with pus. Uterus with hydrometra revealed variably dilated lumen with thin wall or flat in appearance and the variable sized areas of serous fluid accumulation in the endometrial stroma. Uterus with mucometra revealed variably dilated lumen with thin wall and flat in appearance and there was an increase in the number and size of endometrial glands with increased epithelial activity. Uterus with haemorrhages revealed focal areas of haemorrhages in the endometrium or focal areas of hemosiderosis in the endometrial stroma. It was concluded that the natural occurrence of the uterine affections can adversely affect the reproductive performance in sheep and goats.